Pengaruh Kepatuhan Sak, Salah Saji Material, Reputasi Kap Terhadap Financial Distress Dan Opini Audit Pada Perusahaan Manufaktur Yang Terdapat Di Bursa Efek Indonesia (Bei) Tahun 2019-2020 - Merciana Selvi Lasdin; Tri Ratnawati (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of IFR Compliance, Material Misstatement of Public Accounting Reputation on Financial Distress and Audit Opinion. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. There were 24 companies with 72 samples in this study. This research data analysis and hypothesis testing technique uses Partial least square application analysis with Outer Model and Inner Model tests.The results of this study prove that SAK Compliance has a positive and significant effect on Audit Opinion, Material misstatement has a positive and significant effect on Audit Opinion, KAP Reputation does not have a significant effect on Audit Opinion, SAK Compliance does not have a significant effect on Financial Distress, Material Misstatement does not have a significant effect on Financial Distress, KAP Reputation has a positive and significant effect on Financial Distress and Financial Distress does not have a significant effect on the Audit Opinion.